Freedom's battle : the origins of humanitarian intervention - Bass, Gary Jonathan, 1969- (New York : Vintage, 2009)
Author Bass shows that there is an international tradition, reaching back more than two hundred years, of humanitarian intervention--confro nting the suffering of innocent foreigners. Bass describes the politica l and cultural landscapes out of which these activists arose, as an eme rgent free press exposed Europeans and Americans to atrocities taking p lace beyond their shores and galvanized them to act. He brings alive a century of passionate advocacy in Britain, France, Russia, and the Unit ed States. He tells the stories of the activists themselves: Byron, Ben tham, Madison, Gladstone, Dostoevsky, and Theodore Roosevelt among them . Bass also demonstrates that even in the imperialistic late nineteenth century, humanitarian ideals could play a significant role in shaping world politics, and argues that the failure of today's leading democrac ies to shoulder such responsibilities has led to catastrophes such as t hose in Rwanda and Darfur--catastrophes that he maintains are neither i nevitable nor traditional.--From publisher description.
Introduction -- Humanitarianism or imperialism? -- Media and solidar ity -- The diplomacy of humanitarian intervention -- Greeks -- The Gree k revolution -- The Scio massacre -- The London Greek committee -- Amer ica and the Greeks -- Lord Byron's war -- Canning -- The Holy alliance -- A rumor of slaughter -- Navarino -- Syrians -- France under the seco nd empire -- The massacres -- Public opinion -- Occupying Syria -- Miss ion creep -- Bulgarians -- The Eastern question -- Pan-slavism -- Bosni a and Serbia -- Bulgarian horrors -- The Russo-Turkish war -- The Midlo thian campaign -- Conclusion -- Armenians -- The uses of history -- The international politics of humanitarian intervention -- The domestic po litics of humanitarian intervention -- A new imperialism?.
Includes bibliographical references (p. 383-481) and index.
Keywords: Humanitarian intervention -- History; Humanitarian intervention -- Case studies